ANALISIS SEMIOTIKA PADA PUISI “PELAYARAN TUHAN” KARYA AFRIZAL MALNA - Thabroni, Gamal; Wikanengsih, Wikanengsih; Kartiwi, Yesi Maylani (IKIP Siliwangi, 2020)
This research is motivated by the difficulty in appreciating a poetry that uses a lot of indexes and symbols that are rarely used and not yet known by the public such as in the work of